Genome Evolution of a Symbiont Population for Pathogen Defense in Honeybees. (20th October 2022) - Dyrhage, Karl; Garcia-Montaner, Andrea; Tamarit, Daniel; Seeger, Christian; Näslund, Kristina; Olofsson, Tobias C; Vasquez, Alejandra; Webster, Matthew T; Andersson, Siv G E
Abstract: The honeybee gut microbiome is thought to be important for bee health, but the role of the individual members is poorly understood. Here, we present closed genomes and associated mobilomes of 102 Apilactobacillus kunkeei isolates obtained from the honey crop (foregut) of honeybees sampled from beehives in Helsingborg in the south of Sweden and from the islands Gotland and Åland in the Baltic Sea. Each beehive contained a unique composition of isolates and repeated sampling of similar isolates from two beehives in Helsingborg suggests that the bacterial community is stably maintained across bee generations during the summer months. The sampled bacterial population contained an open pan-genome structure with a high genomic density of transposons. A subset of strains affiliated with phylogroup A inhibited growth of the bee pathogen Melissococcus plutonius, all of which contained a 19.5 kb plasmid for the synthesis of the antimicrobial compound kunkecin A, while a subset of phylogroups B and C strains contained a 32.9 kb plasmid for the synthesis of a putative polyketide antibiotic. This study suggests that the mobile gene pool of A. kunkeei plays a key role in pathogen defense in honeybees, providing new insights into the evolutionary dynamics of defensive symbiont populations.